Izgradnja knjižnične zbirke v knjižnici na Glasbeni šoli Jesenice - Jamar, Nina (Knjižnica, 2020)
Purpose: The construction of a library collection at the Music School Jesenice is being described with some emphasis how the library collection should develop in future. Methodology/approach: The library collection was presented according to the activities that form a planned and systematic process of its development. Results: The acquisition of the material must be in accordance with the number of pupils that attend classes at each individual instrument. The goal is that the turn of the material at Music School Jesenice should achieve value 1. Research limitations: We do not know how the library collection at Music School Jesenice developed before 2003. The data how the material was obtained nor about the value for individual unit of library material included in the library collection before 2003 are not known. Originality/practical implications: The researched helped to understand the theoretical starting points related to the construction of library collections. The theoretical background was compared to the actual situation at Music School Jesenice library. The data will be used for future changes and improvements to increase the relevance of Music School Jesenice library collection and to meet the needs of teachers and students of Music School Jesenice.
Keywords: collection development; glasbene knjižnice; izgradnja knjižnične zbirke; music libraries; school libraries; šolske knjižnice